The world economy - Maddison, Angus; Organisation for Economic Co-operation and Development. Development Centre Studies (Paris : OECD, 2006)
This publication brings together two reference works by Angus Maddison: The World Economy: A Millennial Perspective, first published in 2001 and The World Economy: Historical Statistics, published in 2003. This new edition contains Statlinks, a service providing access to the underlying data in Excel® format. These two volumes bring together estimates of world GDP for the past 2000 years and provide perspective on the rise and fall of economies historically.--Publisher description
vol. 1. A millennial perspective - vol.2. Historical statistics
Volume 1: a millennial perspective ; Volume 2: Historical statistics
'Contains statlinks'--Cover
'... brings together two reference works by Angus Maddison: The world economy: a millennial perspective, published in 2001 and The world economy: historical statistics, which was released in 2003.'--Foreword
This new edition contains StatLinks, which allow you to download the tables in Excel format.'--P. [4] of cover
Includes bibliographical references (p.645-653)
Keywords: Economic history; International economic relations -- History; Population -- History; Income distribution -- History; Economic development -- History; International economic relations -- Statistics; Population -- Statistics; Gross domestic product -- Statistics